2016 IEEE Symposium on Service-Oriented System Engineering (SOSE) 2016
DOI: 10.1109/sose.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Monic Testing of Web Services Based on Algebraic Specifications

Abstract: Web services are designed to be discovered and composed dynamically, which implies that testing must also be done dynamically. This involves both the generation of test cases and the checking of test results. This paper presents algorithms for both of these using the technique of algebraic specification. It focuses in particular on the problem that web services, when they are third-party, have poor controllability and observability, and introduces a solution known as monic floating checkable test cases. A prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another advantage of algebraic specification is that it enables automated testing of software against formal specifications [23], [24]. These test automation techniques can be applied to the implementation of system security design formally specified in algebraic specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of algebraic specification is that it enables automated testing of software against formal specifications [23], [24]. These test automation techniques can be applied to the implementation of system security design formally specified in algebraic specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Algebraic speci cations have been used for test automation since the early 1980s. ey have been developed for testing procedural programs (Gonnon et al, 1981;Bernot et al, 1991), object oriented programs (Doong and Frankl, 1994;Hughes and Sto s, 1996;Chen et al, 2001aChen et al, , 1998a, component-based systems (Kong et al, 2007;Yu et al, 2008), and more recently for service-oriented systems (Liu et al, 2016). e research on metamorphic testing demonstrated that such axioms can be useful for testing so ware even if they do not form a complete set of axioms, though the la er are o en required by test tools that automate so ware testing from algebraic speci cations (Chen et al, 2001a(Chen et al, , 1998a.…”
Section: Metamorphic Testingmentioning
confidence: 99%
“…For example, test case generation techniques and tools [1] like fuzz testing [25], data mutation testing [22], random testing [2], adaptive random testing [8,17], combinatorial testing [21] and model based test case generators are all test morphisms, which can be wrapped as seed makers or datamorphisms. Metamorphic relations in metamorphic testing [7] and formal specification-based test oracles [4,5,6,28,15,16] are metamorphisms. Test coverage measurement tools like [24] are test set metrics.…”
Section: Related Workmentioning
confidence: 99%